2010
DOI: 10.1007/s10439-010-9944-2
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Body Surface Potential Map in Computerized Optimization of Biventricular Pacing

Abstract: Biventricular pacing (BVP) could be improved by identifying the patient-specific optimal electrode positions. Body surface potential map (BSPM) is a non-invasive technique for obtaining the electrophysiology and pathology of a patient. The study proposes the use of BSPM as input for an automated non-invasive strategy based on a personalized computer model of the heart, to identify the patient pathology and specific optimal treatment with BVP devices. The anatomy of a patient suffering from left bundle branch b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Briefly, the approach consists of simulating electrical activation in a realistic BiV anatomy for different AVD and VVD as well as several different lead locations and minimizing the error between the obtained activation sequences for each case against a simulated physiological case to determine which combination of AVD, VVD, and lead location yields the best acute response to CRT [ 70 73 , 81 ]. Such models have demonstrated that patient-specific optimization of lead location and AVD and VVD can improve CRT efficacy and impact treatment success [ 31 , 70 , 73 ] and that the use of body surface potential maps can further improve in-silico CRT optimization [ 82 ].…”
Section: Electrophysiology Modelsmentioning
confidence: 99%
“…Briefly, the approach consists of simulating electrical activation in a realistic BiV anatomy for different AVD and VVD as well as several different lead locations and minimizing the error between the obtained activation sequences for each case against a simulated physiological case to determine which combination of AVD, VVD, and lead location yields the best acute response to CRT [ 70 73 , 81 ]. Such models have demonstrated that patient-specific optimization of lead location and AVD and VVD can improve CRT efficacy and impact treatment success [ 31 , 70 , 73 ] and that the use of body surface potential maps can further improve in-silico CRT optimization [ 82 ].…”
Section: Electrophysiology Modelsmentioning
confidence: 99%
“…Physiological signals, particularly those obtained through seamless sensing through wearable or home monitoring [85]- [88] and those obtained through invasive interventional sensors [89]- [92] can provide essential information to personalized models [93]. The former, contribute relevant information on the biorhythms, lifestyle or environmental factors from patients while the latter provide information on the immediate physiological response to specific therapeutic actions thus enabling therapy optimization during delivery.…”
Section: ) Integration and Fusion Of Multimodal Imaging And Multidimmentioning
confidence: 99%
“…The most prominent efforts in this field are the optimization of RF-ablation in case of AF [13], [14] and the optimization of cardiac resynchronization therapy [15]- [18].…”
Section: Introductionmentioning
confidence: 99%